A worldwide population study of the Ag-system haplotypes, a genetic polymorphism of human low-density lipoprotein. - Breguet, G (1990)
The aim of this investigation is to examine the distribution of the Ag immunological polymorphism in human populations on a worldwide scale and to look for possible explanations of this distribution in the field of modern human peopling history and Ag-system evolution. Extensive Ag-antigene typings were carried out on 13 human population samples, including sub-Saharan African, European, west and east Asiatic, Melanesian, Australian aborigine, and Amerindian groups. Complete Ag-haplotype frequencies were estimated by maximum-likelihood-score procedures, and the data were analyzed by genetic distance computations and principal coordinate projections. With the exception of the Amerindian sample, the Ag polymorphism is shown to be highly polymorphic in all the populations tested. Their genetic relationships appear to be closely correlated to their geographical distribution. This suggests that the Ag system has evolved as a neutral or nearly neutral polymorphism and that it is highly informative for modern human peopling history studies. From the worldwide Ag haplotypic distributions, a model for the Ag molecular structure is derived. According to this model and to the most recent results obtained from molecular data, the establishment of the Ag polymorphism could be explained by several mutations and recombination events between the haplotypes most frequently found in human populations today. As a conclusion, genetic and paleontological data suggest that the genetic structure of caucasoid populations (located from North Africa to India) may be the least differentiated from an ancestral genetic stock. Worldwide genetic differentiations are properly explained as the results of westward and eastward human migrations from a Near East-centered but undefined geographical area where modern humans may have originated. The importance of Ag polymorphism analyses for the reconstruction of human settlement history and origins is discussed in the light of the main conclusions of the most recent genetic polymorphism studies.